Nitric oxide oxidation products in the serum of patients with gastric and esophageal cancer and Helicobacter pylori - M. Kürşat TÜRKDOĞAN; Haluk TESTERECİ and Tahir KAHRAMAN and F. Hüsniye DİLEK and Emel AKMAN (Turkish Journal of Gastroenterology, 2019)
-